PENGEMBANGAN ABSENSI ONLINE SECARA REAL TIME ALGORITMA SEQUENTIAL SEARCHING MENGGUNAKAN TEKNOLOGI GPS BERBASIS WEB - Setiawan, Ikbal Danu; Sari, Ratih Titi Komala (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
The attendance application system is important in an era like this, where many large and small companies that initially used fingerprints to be absent or absent manually by admins have now switched to using online attendance. On the one hand, if you are still using manual attendance documents, it is very dangerous to lose or be damaged, therefore there is no web-based use. This attendance is connected to GPS so that the employee's location can be detected when absent. Therefore, Online Attendance in Real Time Sequential Search Algorithm Using Web-Based GPS (Global Positioning System) Technology is very helpful or makes it easier for admins to recap the manpower whether he is not around the office or not. Attendance using this application is very efficient and time-saving and what often happens in small companies is that the employee is no longer there but the employee is not yet in the office, which is detrimental to the company and operations. To make a report using the Online Attendance method in Real Time, Sequential Searching Algorithm Using Web-Based GPS (Global Positioning System) Technology, which requires interviews, research methods, and libraries. Then the software uses the waterfall method which includes: Design, Needs Analysis, Testing, and then Implementation.